Encyclopedia of space and astronomy - Angelo (Facts on File science library, 2006)
Encyclopedia of Space and Astronomy covers this timely and popular topic in a clear, comprehensive manner. Offering a complete presentation of the main concepts, terms, facilities, and people in astronomy, the encyclopedia pays special attention to space-based astronomy and space exploration. Broad coverage includes terms such as astrophysics, planetary science, and cosmology, as well as both American and international astronomy and space technology. Containing more than 600 entries and 15 essays, as well as approximately 250 black-and-white photographs and line illustrations, this authoritative reference provides students and teachers with a visually stimulating learning experience. Encyclopedia of Space and Astronomy focuses mainly on modern astronomy and space achievements but also includes the most important accomplishments of classical astronomy. The impact of astronomy, astrophysics, and cosmology is presented in terms of the development of the scientific method and also with respect to philosophy. History-related entries trace the evolution of astronomy and space technology from ancient times, and selected entries discuss important observatories and organizations such as NASA, as well as contemporary events.